Disentangling the Effects of Bounding and Mobility on Reports of Criminal Victimization - Addington, Lynn A. (Journal of quantitative criminology, 2005)
Replacement respondents who move into NCVS households after the initial bounding interview can introduce measurement error since their reports of victimization may be influenced by their mobility (actual experiences) and by their unbounded interview status (response error). Which of these factors affects reporting is unknown and is the focus of this research. The availability of incoming respondent data from the NCVS School Crime Supplement and mobility status from the NCVS provides a unique opportunity to study these effects separately. Both bounding and mobility were found to influence reporting; however, this influence was not consistent. Unlike findings from past research, bounding only had significant effects on reports of property victimization. Conversely, moving only significantly affected reports of violent victimization. As this study is the first to disentangle the effect of unbounded interview status from mobility on reports of victimization, the findings emphasize the need for further research to better understand these issues.